A spatial reference and identification system for coastal ice-free land in East Antarctica. (12th August 2021) - Southwell, Colin; Smith, David; Bender, Angela; Emmerson, Louise
Abstract: We describe a spatial reference system that uniquely identifies 4884 coastal island and continental rock features across East Antarctica. The system comprises a series of maps and a related database, and can be a foundation tool for a wide range of environmental studies.